The Campus Canopy. 1934-11-14 - Georgia State Womans College (Valdosta State University Archives and Special Collections, 1934)
Privileges Granted Honor Students; Poet Speaks Today; Work on Book is Begun; Dr. W.A. Smart Will Pay Annual Visit; Art Club Exhibit; Swimming Pool and Dormitory Assured; Students Vote to Revise Honor Code;
### Names Mentioned ### W. A. Smart; Frank Reade; Carolyn Brim; Helen Carter; Emily Fluker; Anderson M. Scruggs; Thomas Moults; Elizabeth Larisey; Louise Ambos; Estelle Roberts; Marjorie Groover; Helen Claire Varnedoe; Eleanor Bailey; Winnie Davis; Frances Garbutt; Frances Hinson; Joyce Tipton; Willene Rob; Anne Turner; Mary Elizabeth Weath; Joseph K. Hart; Lena J. Hawks; Leonora Dufour; Philip Weltner; Leonora Dufour; Camille Rogers; Mary Nell Carlyle; Doris Young; Priscilla Kelley; Leila Urquhart; Amanda Barksdale; Carol Forrester; Mary Agnes Roane; Ruth Williams; Grace Lahey; Una Ritch; Leila Mae Tyson; Mary Nell; Margaret Varn; Marion Ried; Catherine The Great; Wiggs; Fred Astaire; Ginger Rogers; Ann Harding; John Shand; Helen Hayes; Lady Sybil Tenderden; Jean Parker; Shirley Temple; Tom Mix; Buck Jones; Ken Maynard; Marian Farbar; Daisy Daniel; Jere Pound; Marian Farbar; Harold"-gulliver; Margaret Joiner; Dorothy Andrews; Eva Martin; Louise Mcmichael; Cleo Barber; Lillian Bragg; Mary Ellen Cordes; Louise Elrod; Leila Mae Tyson; Margaret Zipplies; Mildred Ogles; Broun Hutch; Mary Perry; Jessie Langdale; Estelle Roberts; Mary Lois Hitch; Caroline Parrish; Virginia Ingram; Helen Claire Varnedoe; Emily Woodward; Harold Gulliver; Margaret Carter; Ethlyn Massey; Una Ritch; Henry Kate Gardner; Marguerite Mccall; Mary Thomas; Shelly Sparks; Clara Davis Adams; Ruth Hatcher; Alexa Daley; Mildred Turnbull; Mary Askew; Carol Forrester; Myra Hackett; Margaret Kennedy; Joe Durrenberger; R. H. Powell; Betsy Powell; Caroline Parrish; Regent S. H. Morgan; Carolyn Brim; Emma Ambos; Ruth Jones; Henry Kate Gardner; Esther Smith; Carolyn Cook; Shelly Sparks; Manelle Vincent; Camille Rycroft; Barbara Hatcher; Evelyn May; Permelia Oliff; Clara Davis Adams; Myra Hackett; Ruby Harrison; Leonora Ivey; Doris Young; Lois Hafford; Chappie Bragg; Clare Lawson; Lorene Johnson; L. R. Siebert; Andrew Kingery; Mary Elizabeth Weatherford; Ruth Loughridge; Rugh Bunn; Manelle Vincent; Alvata Carter; Barbara Hatcher; Carolyn Greene; Ruth Williams; Lois Dickerson; Kitsie Smith; Annie Laurie White; Winifred King; Harriet Rogers; Henry Kate Gardner; Marjorie Groover; Grace La; Elizabeth Larisey; Annie Belle Weatherford; Mary Elizabeth Weatherford; Cleo Barber; Amanda Barksdale; Louise Hardy; Broun Hutchinson; Ruth Jones; Ola Lee Powi; Camille Rogers; Doris Young; Mary Alderman; Emma Ambos; Lillian Bragg; Mary Nell; Martha Gay; Josephine Joubert; Marian Reid; Pearl Wilson; Virginia Sheppard; ### Places Mentioned ### Ashley Hall (Valdosta State University); Athens, Georgia; Atlanta, Georgia; Bainbridge, Georgia; Camilla, Georgia; Chicago, Illinois; Cordele, Georgia; Dublin, Georgia; Europe; Florida; G. S. W. C.(Georgia State Womans College); Georgia; Hollywood, California; Jacksonville, Florida; Mexico; Moultrie, Georgia; New York City, New York; Newton; Paris, France; Pavo, Georgia; Plains, Georgia; Quitman, Georgia; Russia; Savannah, Georgia; Tampa, Florida; Thomasville, Georgia; Valdosta, Georgia; Vienna; Virginia Sheppard; Virginia; Washington D.C.; West Hall(Valdosta State University); West Point; Jesup, Georgia; ### Organizations Mentioned ### Georgia State Womans College; Columbia University; Fine Arts Club; Wymodausis Club; Poetry of Georgia; Atlanta Writer's Club; University System of Georgia; Public Works Administration; Georgia State; Art Committee; Emory University; Vanderbilt University; The Pine Branch; Pine Cone; Sigma Nu; Sigma Chi house; Scarlet Express; Ritz; Cornell University; Mae West; Texas State University; Georgia School of Technology; Home Economics; University of Georgia; Kappa Delta; Delta Delta Delta; Buskin Club; Sigma Chi Fraternity; Coordinate College; Board of Regents; Student Government Association; Freshman Commission; Virginia Sheppard;
Keywords: Georgia State Womans College; Georgia State Womans College -- Students -- Periodicals; Valdosta State College -- Students -- Periodicals; Newspapers; College student newspapers and periodicals -- Georgia -- Valdosta